SISTEM PENJAMINAN MUTU PENDIDIKAN: ANALISIS KUALITATIF - Andri; Pembangunan, Heldy Ramadhan Putra (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2025)
This study aims to analyze the success of the existing education quality assurance system at Nurhidayah Integrated Islamic High School. This study uses a descriptive method with a qualitative approach. The research was conducted with observation, interview, and documentation approaches as a data collection technique. The results of the study show that the quality assurance system at Nur Hidayah Integrated Islamic High School includes: Determination of quality standards in accordance with the minimum criteria in the National Education Standards and collaborated with the Quality Standards of the Integrated Islamic School Network. The school's Internal Quality Assurance Team consists of the following elements: Principal, Vice Principal, Foundation and School Committee. The success of the quality of education is greatly influenced by the following supporting factors: qualified educators and education personnel, selected students, cooperative guardians, sufficient funding, regular coordination and evaluation meetings by school leaders. Meanwhile, a number of factors inhibiting the achievement of the quality of education can be identified as follows: the understanding of related parties in implementing the quality assurance system is still lacking, the fulfillment of facilities and infrastructure standards is less than optimal, the density of school activities that can affect the learning process that is not optimal so that it is not always in accordance with the learning plan that has been made by the teacher. Abstrak Penelitian ini bertujuan untuk menganalisis keberhasilan sistem penjaminan mutu pendidikan yang ada pada SMA Islam Terpadu Nurhidayah. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Penelitian dilakukan dengan pendekatan observasi, wawancara, dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian meunjukkan bahwa Sistem penjaminan mutu di SMA Islam Terpadu Nur Hidayah mencakup : Penetapan standar mutu sesuai dengan kriteria minimal dalam Standar Nasional Pendidikan dan dikolaborasikan dengan Standar Mutu Jaringan Sekolah Islam Terpadu. Tim Penjamin mutu Internal sekolah terdiri dari unsur : Kepala Sekolah, Wakil Kepala Sekolah, Yayasan dan Komite Sekolah. Keberhasilan mutu pendidikan sangat dipengaruhi oleh faktor pendukung sebagai berikut : pendidik dan tenaga kependidikan yang qualified, siswa yang terseleksi, walimurid yang kooperatif, pendanaan yang cukup, rapat koordinasi dan evaluasi yang rutin oleh pimpinan sekolah. Sedangkan sejumlah faktor penghambat tercapainya mutu pendidikan, dapat diidentifikasi sebagai berikut : pemahaman pihak-pihak terkait dalam melaksanakan sistem penjaminan mutu masih kurang, pemenuhan standar sarana dan prasarana yang kurang optimal, padatnya kegiatan sekolah yang dapat berpengaruh pada proses pembelajaran yang kurang maksimal sehingga tidak selalu sesuai dengan perencanaan pembelajaran yang telah dibuat oleh Guru.